Surfactants and Microbial Aerosol of Urban Particulate Matter (PM10) in Kuala Lumpur City Centre - Nurul Bahiyah Abd Wahid, Suzita Ramli, Noraine Salleh Hudin, Nor Zila Abd Hamid (Tanjung Malim, 2024)
Surfactants and Microbial Aerosol of Urban Particulate Matter (PM10) in Kuala Lumpur City Centre by Nurul Bahiyah Abd Wahid, Suzita Ramli, Noraine Salleh Hudin, Nor Zila Abd Hamid